2017
DOI: 10.1002/jrs.5085
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ isothermal micro‐Raman spectroscopy reveals the activation energy of dehydration in α‐FeOOH

Abstract: A real‐time, isothermal micro‐Raman spectroscopy was developed as a single technique for monitoring the solid state kinetics of dehydration and measuring its activation energy. The technique comprises of acquisition and numerical analysis of a set of isothermal time‐dependent Raman spectra. α‐FeOOH transformation to Fe2O3 in N2 atmosphere was continuously monitored for up to 16 h at three temperatures. Dehydration activation energy of 1.4(1) eV was estimated. The Raman band evolution of two modes with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Analyzing the characteristic peaks of each phase, it can be concluded that magnetite phase occurs in the samples Mag-01 to Mag-04 (Figure 3a) and magnetite and maghemite phases occur in the samples Mag-05 and Mag-06 (Figure 3b). There is good agreement in the reported spectra of goethite [17][18][19] with bands at 92, 164, 203, 243, 297, 384, 478, 546 and 663 cm -1 found in some regions of sample Mag-01 (Figure 3c). Table 2 shows the evaluated synthesis parameters and the obtained crystallite size and crystallinity values for all samples, estimated by Scherrer equation.…”
Section: Powder Characterizationsupporting
confidence: 86%
“…Analyzing the characteristic peaks of each phase, it can be concluded that magnetite phase occurs in the samples Mag-01 to Mag-04 (Figure 3a) and magnetite and maghemite phases occur in the samples Mag-05 and Mag-06 (Figure 3b). There is good agreement in the reported spectra of goethite [17][18][19] with bands at 92, 164, 203, 243, 297, 384, 478, 546 and 663 cm -1 found in some regions of sample Mag-01 (Figure 3c). Table 2 shows the evaluated synthesis parameters and the obtained crystallite size and crystallinity values for all samples, estimated by Scherrer equation.…”
Section: Powder Characterizationsupporting
confidence: 86%
“…This indicates the formation of α-FeOOH. 52,53 Unlike LaNi 0.5 Fe 0.5 O 3, the modes corresponding to La are not clearly distinguishable.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Along with this, very broad and less intense bands appear between 200 and 500 cm –1 . This indicates the formation of α-FeOOH. , Unlike LaNi 0.5 Fe 0.5 O 3, the modes corresponding to La are not clearly distinguishable.…”
Section: Resultsmentioning
confidence: 99%
“…Sendova, Hosterman, and Grebe used in‐situ isothermal micro‐Raman spectroscopy to reveal the activation energy of dehydration in α‐FeOOH. Their study opens new possibilities for developing versatile, solid state chemical and bio‐chemical Raman sensors and advances the field of analytical micro‐Raman spectroscopy . Sun et al reported pressure‐induced Fermi resonance between the fundamental modes in 7,7,8,8‐tetracyanoquinodimethane.…”
Section: High Pressure and Temperature Studiesmentioning
confidence: 99%
“…Their study opens new possibilities for developing versatile, solid state chemical and bio-chemical Raman sensors and advances the field of analytical micro-Raman spectroscopy. [214] Sun et al reported pressure-induced Fermi resonance between the fundamental modes in 7,7,8,8-tetracyanoquinodimethane. The relationship of Fermi resonance parameters (intensity ratio, coupling coefficient, frequency separation, and frequency separation of unperturbed transitions) with pressure was discussed.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%